DAMPAK IKLIM ORGANISASI TERHADAP KEBAHAGIAAN DAN KINERJA KARYAWAN (STUDI PADA UNIVERSITAS MUHAMMADIYAH YOGYAKARTA) - Sigit Ary Wijayanto (Jurnal Bisnis, Manajemen, dan Akuntansi, 2017)
This research is conducted to investigate the influence of organizational climate towards employeeperformance with happiness as intervening variable. The population of the research is all theemployee of Universitas Muhammadiyah Yogyakarta which is 245 employees from 9 faculties and25 units/department. Path analysis was used to analysis the data. The result showed thatorganizational climate is positively influence employee’s performance and there is a finding thatbetter orgnizational climate implies to increase employee’s happiness at work. The implication ofthese finding conlude the article.Keywords : organizational climate, happiness, employee performance